THE STUDY OF EFFECT PROBIOTIC IN ACNE AND ROSACEA : A SYSTEMATIC REVIEW - Novitafalen; Christika, Nathania; Henyta; Azhari, Ririn; Ananda, Astrid; Syarfina, Afdila (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Alternative remedies have long been utilized by patients to treat skin diseases in addition to or instead of traditional medical care. Research on the relationship between probiotics, the skin microbiota, and inflammatory dermatoses is only getting started.Aims : This systematic review is to review the association of probiotic and its effect in acne and rosacea.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 19 articles, whereas the results of our search on SCIENCE DIRECT brought up 166 articles, our search on SAGEPUB brought up 10 articles. The results of the search conducted for the last year of 2014 yielded a total 18 articles for PubMed, 122 articles for SCIENCE DIRECT and 7 articles for SAGEPUB. In the end, we compiled a total of  6 papers, 3 of which came from PubMed, 2 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included six research that met the criteria.Conclusion: In summary, manyof the studies that are currently available in the literature only involved a limited number of patients, did not state which species or dosage of probiotics were utilized, or did not run their trials long enough to fully assess the effects of probiotics on the microbiome of the skin and stomach.